Perceived Barriers to Health-Promoting Behaviors among Nursing Staff Working at Al-Imam Al-Hussein Medical City, Kerbala, Iraq - Ameer Alaa Najaf; Selman Hussein Faris (Kerbala Journal of Nursing and Health Sciences., 2026)
Background: Among the barriers that nurses encounter in their practices include work overloads, working at night and odd hours, which do not allow them to be able to practice health and wellness-promoting behaviors despite understanding what they need to do about health and wellness. Methods: This study utilized a cross-sectional design to identify barriers perceived by nursing staff (n = 300) regarding their health-promoting behaviors and to explore associations with various personal and professional variables. Data were gathered using a structured questionnaire adopted by previous research, encompassing demographics and determinants of health-promoting behaviors. Cronbach's alpha coefficient was used to determine the reliability of the questionnaire. Results: The findings revealed that participation in health-promoting activities had a robust inverse relationship with perceived barriers (r = –.296, P = .001), implying that higher engagement in such activities was associated with lower perceived barriers. Notably, other factors such as sex, age, marital status, qualifications, income, experience, and prior surgeries did not exhibit significant associations. Conclusion: The study concluded that nursing staff confronts moderate barriers, primarily due to logistical challenges like the lack of nearby activity centers and insufficient information about available programs. Further obstacles recognized included environmental aspects like bad weather and personal barriers, such as time constraints from family responsibilities, alongside a lack of motivation. Interestingly, physical limitations were not common barriers among participants.